Critical discourse analysis of news reports on Afghan women in Malaysian newspapers / Nurul Syuhada Badrul Halim, Wan Aisyah Nadiah Wan Azman and Muhammad Hariz Mohammad Hafiz - Badrul Halim, Nurul Syuhada; Wan Azman, Wan Aisyah Nadiah; Mohammad Hafiz, Muhammad Hariz (Universiti Teknologi MARA, Sabah, 2025)
This study analyses the representation of Afghan women in Malaysian newspapers during the Taliban’s 2021 offensive based on Fairclough’s (1988) Critical Discourse Analysis (CDA) framework. It uncovers the underlying linguistic and ideological biases in eight news articles, published by The Star and Free Malaysia Today. The findings indicate that The Star employs objective and formal terminology, while the adoption of a more critical stance was observed in Free Malaysia Today. A varied representation of Afghan women was also observed, and The Star focuses on their professional roles in the community. Meanwhile, Free Malaysia Today portrays them in a victimised manner. Direct and scare quotes were also highlighted, showcasing their roles in reinforcing and challenging dominant ideologies. The research demonstrates the media’s role in shaping one’s social realities and affecting public perception. This study also contributes to critical discourse analysis by producing valuable insights into how marginalised groups are represented during a political crisis. The findings revealed that The Star described Afghan women with professional identities using formal and neutral language while Free Malaysia Today emphasised their victimhood and resistance through the usage of emotionally charged language, showcasing different ideological stances adopted by each platform’s editorial stance. The findings are relevant to language students, future researchers, policy makers, and academicians in linguistics and media studies.